Adopsi Pekebun Karet Terhadap Penggunaan Asam Semut Sebagai Bahan Koagulan Lateks di Kecamatan Pemali Kabupaten Bangka - Ameilia Zuliyanti Siregar (Khazanah Intelektual, 2021)
This study aims to determine the level of adoption of smallholders and the factors that have a significant effect on the adoption of rubber planters in applying formic acid as a latex coagulant in Pemali District, Bangka Regency. This type of research is descriptive quantitative. The data collection methods are observation and interviews using a questionnaire that has been tested for validity and reliability, while the data analysis method uses a Likert scale and Logistics Regression Analysis. The variables used in this study are age, education, land area, characteristics of innovation, the role of extension workers, communication media, facilities and infrastructure, and the role of farmer groups. The results of the study showed that the adoption rate of rubber planters for the use of formic acid as a latex coagulant in Pemali District, Bangka Regency was in the low category with a percentage of 22.95%. The results of the Logistics Regression Analysis showed that there was a significant influence between the variables of innovation characteristics, the role of extension workers, and infrastructure on the adoption opportunities for the use of formic acid as a latex coagulant in Pemali District, Bangka Regency.